Pengaruh Kinerja Pegawai Dalam Pelayanan Kesehatan Di Rumah Sakit Islam Malahayati Medan (Kajian Islamic Hospitality) - Naufal Arib Maulana Hasibuan; Muzakkir; Husnel Anwar (CV Edujavare Publishing, 2025)
This study aims to examine the influence of employee performance on healthcare services at Malahayati Islamic Hospital in Medan from the perspective of Islamic hospitality. The method employed is a descriptive qualitative approach, with data collection techniques including in-depth interviews, direct observation, and documentation. The focus of this research lies in the Islamic values applied in healthcare services, such as courtesy, friendliness, cleanliness, empathy, and spiritual work ethics. The findings reveal that effective employee performance grounded in Islamic hospitality values can enhance service quality, patient comfort, and trust in the hospital. The services provided are not solely oriented toward physical healing but also consider the patients’ spiritual and emotional aspects. Values such as Islamic communication, adherence to standard operating procedures (SOP), provision of halalan tayyiban food, and spiritual support are integral in shaping a humane healthcare system rooted in Islamic ethics